2016
DOI: 10.2337/db15-0291
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prevents Diet-Induced Cellular Senescence in Adipose Tissue

Abstract: Considerable evidence implicates cellular senescence in the biology of aging and chronic disease. Diet and exercise are determinants of healthy aging; however, the extent to which they affect the behavior and accretion of senescent cells within distinct tissues is not clear. Here we tested the hypothesis that exercise prevents premature senescent cell accumulation and systemic metabolic dysfunction induced by a fast-food diet (FFD). Using transgenic mice that express EGFP in response to activation of the senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
181
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 51 publications
12
181
2
1
Order By: Relevance
“…Chronic reductions in TAF + senescent cells are associated with attenuated endothelial dysfunction in aged mice, improved vascular smooth muscle sensitivity to nitric oxide donors in hypercholesterolemic mice, and reduced vascular calcification in hypercholesterolemic mice (Roos et al, 2016). Critically, our group also found that the beneficial cardiovascular effects of chronic exercise training are closely associated with reductions in visceral adipose tissue senescence, suggesting that reducing senescent cell burden at non-cardiovascular sites may have significant benefits through systemic or paracrine factors (Schafer et al, 2016). Collectively, conflicting reports highlight the need for additional studies to understand the mechanistic contribution of senescent cells in individual pathogenic contexts; however, our recent findings demonstrate that targeting senescent cells is a viable strategy to improve age- and obesity-related cardiovascular phenotypes.…”
Section: Cellular Senescence: Aging Mechanism Activated By Nutrienmentioning
confidence: 97%
See 3 more Smart Citations
“…Chronic reductions in TAF + senescent cells are associated with attenuated endothelial dysfunction in aged mice, improved vascular smooth muscle sensitivity to nitric oxide donors in hypercholesterolemic mice, and reduced vascular calcification in hypercholesterolemic mice (Roos et al, 2016). Critically, our group also found that the beneficial cardiovascular effects of chronic exercise training are closely associated with reductions in visceral adipose tissue senescence, suggesting that reducing senescent cell burden at non-cardiovascular sites may have significant benefits through systemic or paracrine factors (Schafer et al, 2016). Collectively, conflicting reports highlight the need for additional studies to understand the mechanistic contribution of senescent cells in individual pathogenic contexts; however, our recent findings demonstrate that targeting senescent cells is a viable strategy to improve age- and obesity-related cardiovascular phenotypes.…”
Section: Cellular Senescence: Aging Mechanism Activated By Nutrienmentioning
confidence: 97%
“…Senescence effector activation was associated with increased SA-β-gal activity, with 12% of adipose cells staining positively, presentation of the SASP, and systemic metabolic disease. Exercise initiated at the same time as the high calorie diet or after accumulation of senescent burden ameliorated these effects (Schafer et al, 2016). In the absence of obesity, age-related adipose tissue atrophy is prevented by transgenic clearance of senescent cells (Xu et al, 2015a).…”
Section: Cellular Senescence: Aging Mechanism Activated By Nutrienmentioning
confidence: 99%
See 2 more Smart Citations
“…This study re‐enforces the importance of dietary interventions for senescence induction or prevention. Indeed, CR was previously shown to reduce senescence in the mouse liver and intestine (Wang et al., 2010), and high‐fat diet was recently implicated in promoting accelerated senescence with detrimental effects in mice (Schafer et al., 2016). Of course, more studies are warranted to understand how lowering calorie intake reduces senescence burden, and whether the reduction in senescence is sufficient to directly lower the levels of various tissue‐remodeling factors and interleukins, which could be affected by several other variables independently perturbed by the presence of senescent cells.…”
Section: Introductionmentioning
confidence: 99%